Pharmacokinetics and safety of two Voriconazole formulations after intravenous infusion in two doses in healthy Chinese subjects - Li, Xin; Wang, Chenjing; Shi, Ping; Liu, Yanping; Tao, Ye; Lin, Pingping; Li, Ting; Hu, Haixun; Sun, Feifei; Liu, Shuqin; Fu, Yao; Cao, Yu (BMC pharmacology & toxicology, 2023)
Voriconazole is a second-generation triazole that is used to prevent and treat invasive fungal infections. The purpose of this study was to evaluate the pharmacokinetic equivalency of a test formulation and reference formulation (Vfend®) of Voriconazole. This was a randomized, open-label, single-dose, two-treatment, two-sequence, two-cycle, crossover phase I trial. The 48 subjects were equally divided into 4 mg/kg and 6 mg/kg groups. Within each group, the subjects were randomized 1:1 to the test or reference formulation.. After a 7-day washout period, crossover formulations were administered. The blood samples were collected at 0.5, 1.0, 1.33,1.42,1.5, 1.75, 2.0, 2.5, 3.0, 4.0, 6.0, 8.0, 12.0, 24.0, 36.0, 48.0 h later in the 4 mg/kg group, while at 0.5, 1.0, 1.5, 1.75, 2.0, 2.08, 2.17, 2.33, 2.5, 3.0, 4.0, 6.0, 8.0, 12.0, 24.0, 36.0, 48.0 h later in the 6 mg/kg group. The plasma concentrations of Voriconazole were determined by Liquid chromatography-tandem mass spectrometry (LC-MS/MS). The safety of the drug was evaluated. The 90% confidence intervals (CIs) of the ratio of geometric means (GMRs) of C , AUC , and AUC in both 4 mg/kg and 6 mg/kg groups were within the prespecified bioequivalence limits between 80 ~ 125%. In the 4 mg/kg groups, 24 subjects were enrolled and completed the study. The mean C was (2.552 ± 0.448) μg/mL, AUC was (11.875 ± 7.157) h*μg/mL and AUC was (12.835 ± 9.813) h*μg/mL after a single dose of 4 mg/kg test formulation. The mean C was (2.615 ± 0.464) μg/mL, AUC was (12.500 ± 7.257) h*μg/mL and AUC was (13.416 ± 9.485) h*μg/mL after a single dose of 4 mg/kg reference formulation. In the 6 mg/kg groups, 24 subjects were enrolled and completed the study. The mean C was (3.538 ± 0.691) μg/mL, AUC was (24.976 ± 12.364) h*μg/mL and AUC was (26.212 ± 14.057) h*μg/mL after a single dose of 6 mg/kg test formulation. The mean C was (3.504 ± 0.667) μg/mL AUC was (24.990 ± 12.455) h*μg/mL and AUC was (26.160 ± 13.996) h*μg/mL after a single dose of 6 mg/kg reference formulation. Serious adverse event (SAE) was not observed. In both 4 mg/kg group and 6 mg/kg group, equivalent pharmacokinetic characteristics that satisfied the criteria of bioequivalence for both test and reference formulations of Voriconazole. NCT05330000 (15/04/2022).